Examining the Correlation between Macroeconomic Factors and Stock Indices: A Comparative Analysis of IHSG and Nikkei - Sim, Yulia Melyanda; Kaluge, David (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
This comprehensive research investigates the intricate relationship between macroeconomic factors and stock market performance, specifically focusing on the Indonesia Stock Exchange Composite Index (IHSG) and the Nikkei Stock Average. Employing a robust quantitative approach, the study emphasizes key variables such as inflation, exchange rates, interest rates, GDP growth, and oil prices, utilizing regression analysis to unravel unique patterns within the Indonesian and Japanese markets. For IHSG, significant negative correlations with inflation highlight its impact on purchasing power and corporate profitability. The non-significant relationship with the Bank Indonesia Interest Rate (BI Rate) emphasizes market resilience to interest rate fluctuations. The significant negative correlation with the Rupiah underscores the pivotal role of currency stability. Additionally, the non-significant relationship with oil prices suggests a limited influence on IHSG movements. Turning to the Nikkei, non-significant relationships with inflation, the Bank of Japan (BOJ) Rate, GDP, exchange rates, and oil prices underscore the diverse factors at play. These findings offer valuable insights for investors, policymakers, and researchers, enriching the understanding of the multifaceted influences shaping the relationship between macroeconomic conditions and stock market dynamics in Indonesia and Japan. The study contributes empirically rich insights, addressing gaps in existing literature and paving the way for informed decision-making in the complex landscape of global financial markets.